Management of capital flows : comparative experiences and implications for Africa - Bhalla, Praveen (UN New YorkUS, 2003)
Focuses on corporate governance, competition, the new international financial architecture and large corporations in emerging markets. Examines the experiences of economies in East and South-East Asia and those of the Organisation of Economic Co-operation and Development. Analyses the situation in the Sub-Saharan African region, particularly with respect to internal and external management.